Harald Sigurdsson and the Russo-Byzantine War of 1043 - Oleksandr M. Fylypchuk (Slovene, 2014)
The present article analyzes Kekaumenos’ commentary on the service of Harald Sigurdsson in the Byzantine army. Special attention is given to the composition of Consilia et Narrationes and the historiographic perception of this text. It then discusses Kekaumenos’ commentary in light of Harald’s adventures in the Haralds saga Siguðarsonar and the story about the attacks of Rus’ in the Byzantine literature. The author attempts to show that Constantine IX Monomachos tried to leave the large groups of mercenaries in Constantinople. Furthermore, the emperor’s attitude to Harald and his warriors was related to the events of Russo-Byzantine war in 1043. Constantine IX Monomachos dispersed these mercenaries into the themes. John Scylitzes wrote that the emperor put a guard over them to prevent them from inciting a rebellion. These arrests could explain Harald’s mysterious detention in the reign of Constantine IX Monomachos. It is possible to conclude that Harald’s detention was caused by the Russo-Byzantine war in 1043.